2005
DOI: 10.1007/s10791-005-6617-0
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary Radial Basis Functions for Credit Assessment

Abstract: Credit analysts generally assess the risk of credit applications based on their previous experience. They frequently employ quantitative methods to this end. Among the methods used, Artificial Neural Networks have been particularly successful and have been incorporated into several computational tools. However, the design of efficient Artificial Neural Networks is largely affected by the definition of adequate values for their free parameters. This article discusses a new approach to the design of a particular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 51 publications
(59 reference statements)
0
16
0
Order By: Relevance
“…For finance applications, evolutionary clustering algorithms have been used to group either customer or company profiles, as in the works from Lacerda et al [87], for credit risk assessment, and Krovi [84], for cluster analysis of bankrupt and non-bankrupt companies.…”
Section: Applicationsmentioning
confidence: 99%
“…For finance applications, evolutionary clustering algorithms have been used to group either customer or company profiles, as in the works from Lacerda et al [87], for credit risk assessment, and Krovi [84], for cluster analysis of bankrupt and non-bankrupt companies.…”
Section: Applicationsmentioning
confidence: 99%
“…Since genetic algorithms are basically an optimization heuristic, Lacerda et al (2005) investigate the use of RBF neural networks designed by means of genetic algorithms and concluded that such an implementation is superior (lowest average classification error and smallest average number of hidden nodes) to other methods in a credit assessment application. Besides, while the other techniques have their parameters defined by a trial-and-error iterative process, the genetic-based approach automatically searches for the parameters of the RBF neural network.…”
Section: Parameter Optimizationmentioning
confidence: 99%
“…On the other hand, some papers (Lacerda et al, 2005;Hoffmann et al, 2007;Martens et al, 2007;de Pinho et al, 2009;Oreski et al, 2012) include the paired t-test for assessing statistical significance of difference, but this appears to be conceptually inappropriate and statistically unsafe because parametric tests assume independence, normality, and homogeneity of variance, which are often violated due to the nature of the problems (Demsˇar, 2006).…”
Section: Statistical Significance Testsmentioning
confidence: 99%
“…Evolutionary algorithms have been used for the design of RBFNs (Buchtala et al 2005;Harpham et al 2004;Lacerda et al 2001Lacerda et al , 2005 reviews can be found) but existing approaches typically suffer from the problems of a high runtime and a premature convergence in local minima. Those are both objectives to reach in any evolutionary proposal for the design of RBFNs.…”
Section: The Design Of Radial Basis Function Networkmentioning
confidence: 99%